Analysis of Errors Made by Iraqi University Students in the Area of English Relativization System - Naethel, Abbas (International Journal of Language and Literary Studies, 2020)
This study aims at giving an account of an analysis of errors made by Iraqi university students in the area of English Relativization system. It focuses mainly on dealing with the investigation of the syntactic errors committed by Iraqi students in English relative clause. This causes a major problem for university students learning English as a foreign language. This comes from the students' interlingual and intralingual strategies. This also indicates that the university students seem to depend on the target language (TL) system rather than on that of the native language (NL). The technique used is an error analysis which Wilkins (1972) highlights its value in giving "greater understandings of the difficulties that learners face, and will perhaps assist in the development of pedagogic strategies." (p. 206). After analyzing and interpreting the errors made in the 100 students' compositions, some recommendations are given.